Analysis of E-learning Program's Role in Physical Learning (Journal of Advances in Information Systems and Technology, 2020)
This study aimed to determine the application of e-learning programs, the role of e-learning programs, and how important the e-learning program's role in Physical learning was. This research used descriptive study using 80 students of the odd semester in 2016/2017 and 2017/2018 academic study program. The data obtained by questionnaires then analyzed based on the specified categories. From the data processing, it was proved that e-learning programs could be applied through e-learning modules. The program's role was in the "moderately contribute" category with a 3.44 score (scale 1 -5). The relation of e-learning program with its role in Physical learning based on the theoretical (based on calculations using formulas) mean that for the moderate, high/strong, and very high/very strong category was equal to 91.25%, for low/weak category was equal to 8.75%. Based on the data, it means that for moderate, high/strong, and very high/very strong category was equal to 76.25%, whereas for low/weak and very low/very weak category was equal to 23.75%.